2022
DOI: 10.1186/s12891-022-05366-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative dynamic quantitative sensory testing in remote pain-free areas is associated with axial pain after posterior cervical spinal surgeries

Abstract: Background Postoperative axial pain (PAP), characterized by pain and/or stiffness around the posterior neck, periscapular areas and/or shoulder region, is a vexing complication affecting 5–60% of patients undergoing posterior cervical decompression. Given its relatively high frequency and negative impact on patients’ physical and mental status, efforts preoperatively to confirm patients at risk of developing PAP to offer more efficient pain management to minimize this complication have a high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…In light of the fact that the expression of wind up at spinal cord neurons may be genetically encoded (62), an enhanced TSP may be viewed as an indicator of higher propensity to developing pain hypersensitivity. In support of this notion, a number of studies have shown TSP to be a predictor of pain prospectively (63)(64)(65). From a neurophysiological standpoint, temporal summation is considered as one of the initiating neuroplastic mechanisms of central sensitization (66,67).…”
Section: Discussionmentioning
confidence: 93%
“…In light of the fact that the expression of wind up at spinal cord neurons may be genetically encoded (62), an enhanced TSP may be viewed as an indicator of higher propensity to developing pain hypersensitivity. In support of this notion, a number of studies have shown TSP to be a predictor of pain prospectively (63)(64)(65). From a neurophysiological standpoint, temporal summation is considered as one of the initiating neuroplastic mechanisms of central sensitization (66,67).…”
Section: Discussionmentioning
confidence: 93%
“…Considering that the expression of wind-up at spinal cord neurons may be genetically encoded [ 71 ], an enhanced TSP may be viewed as an indication of higher propensity to developing pain hypersensitivity. In support of this notion, a number of studies have shown TSP to be a predictor of pain prospectively [ 72 74 ]. From a neurophysiological standpoint, temporal summation is considered as one of the initiating neuroplastic mechanisms of central sensitization [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 98%
“…This finding is in line with previous study conducted by Zhang et.al. in which they conducted quantitative sensory testing and revealed that patients with PAP have a lower pressure pain threshold and temporal summation (i.e., higher sensitivity to pain perception) than patients without PAP. Their findings indicated that preoperative endogenous pain modulation deficiency might be associated with axial pain after posterior cervical decompression [9]. It is not surprising that DCM patients developed abnormal pain modulation system, considering most of the patients experienced chronic pain that is associated with modifications of the central nervous system, such as central sensitization, which is responsible for alterations in pain sensitivity in acute and chronic pain situations [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no effective perioperative management to prevent or reduce this vexing complication and thus needs further investigation for its potential mechanism [ 8 ]. Recently Zheng et al investigated the pressure pain thresholds, temporal summation and conditioned pain modulation in DCM patients and found that preoperative endogenous pain modulation deficiency may be associated with axial pain after posterior decompression surgery indicating preoperative pain hypersensitivity in DCM might contributed to the prevalence of PAP [ 9 ]. However, the brain mechanism underlying such phenomenon is still unknown.…”
Section: Introductionmentioning
confidence: 99%